2000
DOI: 10.3354/ame021257
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of natural Antarctic marine microbial assemblages to ambient UV radiation: effects on bacterioplankton

Abstract: Seasonal ozone depletion over Antarctica leads to enhanced UVB (280 to 320 nm) radiation throughout the period of greatest biological production. The effect of UV radiation on bacterioplankton has received little attention, and its effects on marine microheterotrophs and viruses, which mediate bacterial biomass, are poorly understood. This study examined the impact of ambient solar W radiation on bacterioplankton in natural Antarctic microbial communities. Following a lag of 2 d, bacterial concentrations incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 24 publications
(33 reference statements)
4
42
1
Order By: Relevance
“…Nevertheless, whereas these authors found this recovery at moderately low intensities of UVA and PAR, we only detected it at high light intensities (i.e., at upper depths). Our results were in line with the finding by Davidson and van der Heijden (2000) that bacteria in whole water were able to repair UV-induced damage and grow while residing in near-surface waters in Antarctic. In light of the above considerations, we conclude that the net effect of full sunlight (stimulatory or inhibitory) on bacterial activity at upper depths is the result of interplay between the detrimental effects of UVB and the recovery processes promoted by UVA and PAR.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, whereas these authors found this recovery at moderately low intensities of UVA and PAR, we only detected it at high light intensities (i.e., at upper depths). Our results were in line with the finding by Davidson and van der Heijden (2000) that bacteria in whole water were able to repair UV-induced damage and grow while residing in near-surface waters in Antarctic. In light of the above considerations, we conclude that the net effect of full sunlight (stimulatory or inhibitory) on bacterial activity at upper depths is the result of interplay between the detrimental effects of UVB and the recovery processes promoted by UVA and PAR.…”
Section: Discussionsupporting
confidence: 83%
“…Bacterial standing-stock parameters and bacterial production yielded values near the lower limit of the range reported (Reche et al 1996;Straskrabová et al 1999a;Davidson and van der Heijden 2000). Because our main objective was to evaluate the effect of spectral composition of solar radiation on the algae-bacteria relationship, mimicking the natural environment, we simultaneously exposed bacteria (in whole water) and [ 3 H]TdR to solar radiation in situ in our experimental approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of UV radiation on the natural protist community was determined using aliquots of the same samples used to determine the previously published effect of UV on the bacterioplankton. For detailed methods of sample acquisition, preparation and incubation see Davidson & van der Heijden (2000).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have revealed that UVR can negatively affect the growth (Nilawati et al 1997;Davidson and van der Heijden 2000) and photosynthetic rates (Roos and Vincent 1998;Litchman et al 2002) of phytoplankton and can alter phytoplankton community composition (Karentz et al 1991;Cabrera et al 1997). However, a number of studies have also indicated a lack of effect of UVR on the growth rates of algae (Halac et al 1997).…”
mentioning
confidence: 99%